Diseño de un plan de responsabilidad social para la Mutualista Imbabura situada en la ciudad de Ibarra-provincia de Imbabura - Barahona Erazo, Edgar Esteban (2015)
The economic-industrial development has lead society to become agents of their own uncertainty, the use of natural resources and an accelerated land degradation has caused that organizations in the public and private sectors involved in a responsible participation in the problems generated by the productive and commercial activities. Social responsibility seeks to balance the benefit of generating economic returns from business activities and social impact generated after meeting the expectations of shareholders, environment, employees and community. For the next investigation for Mutualista Imbabura located in the city of Ibarra Imbabura province was used, here the design of a social responsibility plan that seeks to improve the relationship with the internal and external environment of the institution by undertaking shown campaigns interaction with employees and the community at large as well as care for the environment showing that shareholders can provide a better working environment and a good social environment with the community, which as a result improve the quality of service plus satisfaction of their employees and improve their corporate image. Social responsibility is the role that organizations have to play in order to achieve competitive advantage and integrate the vast network of organizations worldwide seeking a responsible management in economic, social and environmental.